ANALISIS PERFORMA KOLEKTOR SURYA PELAT DATAR DENGAN SIRIP MELINTANG BERONGGA DISUSUN STAGGERED - Juliarto, Agil Yanuar; Astawa, Ketut; Sucipta, Made (Teknik Desain Mekanika; Vol 13 No 3 (2024): Juli 2024 : Teknik Desain Mekanika, 2024)
Abstract The geographical location that affects the course of the sun makes Indonesia experience a tropical climate that results in receiving solar radiation almost all year round. One of the purposes of utilizing solar energy is for drying. Although natural drying is often used, it is less effective as it takes place in open fields and is affected by weather changes that can hinder the drying of crops and increase the risk of contamination with chemicals, dust, and dirt. Therefore, there is an interest to utilize the potential of solar energy by using a solar collector device that aims to collect heat by keeping the hot air clean during the drying process. This study aims to improve the performance of a flat plate solar collector using an underflow absorber with hollow transverse fins of square shape arranged staggered by experimental method. This experiment was conducted to observe the fluid flow and heat transfer phenomena occurring in the solar collector. To improve the performance of the solar collector, variations will be given with a mass flow rate variation of 0.0009; 0.0019; and 0.0023 kg/s at a temperature of 32 ?C. The results showed that in a flat plate solar collector with hollow transverse fins in the shape of a square arranged staggered there is a temperature distribution from the reflection of the glass to the bottom plate of the collector. The temperature distribution phenomenon that occurs in solar collectors is found that the low mass flow rate makes the temperature in the collector section higher than the high mass flow rate. The highest useful energy was obtained in the ?.3 variation with useful energy of 50.45 W and the highest efficiency of 8.93%. The average useful energy and average efficiency are in the ?,3 variation of 33.47 W and 5.76%. This shows that the variation in mass flow rate has a significant difference in value to the temperature distribution in the collector section, useful energy, and efficiency of the solar collector performance. Keywords: Hollow transverse fin, Square cavity, Staggered, Temperature distribution, Useful energy, Efficiency.